Infrastructure project planning decision making: Challenges for decision support system applications - Omar, Mohd Faizal; Trigunarsyah, Bambang; Wong, Johnny (2009)
Most infrastructure project share the same characteristics in term of management aspects and shortcomings.Human factor is believed to be the major drawbacks due to the nature of unstructured problems which can further contribute to management conflicts.This growing complexity in infrastructure projects has shift the paradigm of policy makers to adopt Information Communication Technology (ICT) as a driving force.For this reason, it is vital to fully maximise and utilise the recent technologies to accelerate management process particularly in planning phase.Therefore, a lot of tools have been developed to assist decision making in construction project management.The variety of uncertainties and alternatives in decision making can be entertained by using useful tool such as Decision Support System (DSS).However, the recent trend shows that most DSS in this area only concentrated in model development and left few fundamentals of computing.Thus, most of them were found complicated and less efficient to support decision making within project team members. Due to the current incapability of many software aspects, it is desirable for DSS to provide more simplicity, better collaborative platform, efficient data manipulation and reflection to user needs.By considering these factors, the paper illustrates four challenges for future DSS development i.e. requirement engineering, communication framework, data management and interoperability, and software usability.